Pendekatan Andragogi dalam Pembelajaran Maharah Al-Kitabah di LPBA Nurul Jadid - Moh Ulum; Laialatul Hadawiah (INAIFAS PRESS, 2022)
LPBA Pondok Pesantren Nurul Jadid Probolinggo has implemented an andragogy approach in learning mahārah al-kitābah. This research oriented to measure the effectiveness of andragogy implementation in mahārah al-kitābah learning at LPBA. In this research, the researcher conducted qualitative and quantitative approaches. Researcher collected data through interview techniques, observation, documentation, tests, and also questionnaires. The object of the research was LPBA students. Through this research, it was found that 1) the learning process using an andragogy approach was more effective and had a great influence on students who were shown to easily express their ideas or feelings in written form; 2) the test results showed that the respondents were declared complete 100% in the mastery of compiling correct sentences in accordance with the rules of Arabic writing; and 3) based on the results of a questionnaire, an average of 80% stated